Disaster Oriented Tourism Planning: Risk Management and Vulnerability Assessment by Using Geographic Information System - Dr. Madhumita Mukherjee,Dr. Nishikant Kumar; Mr. Ravi Kshirsagar, Mr. Chetan Mungantiwar; Dr. Sudipta Mukherjee (European Economic Letters (EEL), 2025)
Disaster-oriented tourism planning is a critical aspect of sustainable tourism development, aiming to minimize the negative impacts of disasters on tourism destinations while ensuring the safety of tourists and local communities. This article presents a comprehensive study on disaster-oriented tourism planning, focusing on risk management and vulnerability assessment using the most modern technology, Geographic Information Systems (GIS). The research explores the intricate relationship between tourism and disasters, highlighting the vulnerability of tourism destinations to various hazards such as natural disasters. It enhances the need for a proper scientific planning and preparedness to mitigate the future risks and ensure the solution of the tourism sector. The study explores a GIS-based approach to assess the vulnerability of tourism destinations to different hazards. GIS is utilized to collect, analyze, and visualize spatial data related to hazard occurrence, infrastructure, demographics, and tourism assets. By integrating these data layers, the research identifies areas of high vulnerability and assesses the potential impacts of disasters on tourism infrastructure, economic activities, and community well-being. Furthermore, the research examines various risk management strategies and their application in disaster-oriented tourism planning. East Sikkim is taken as a study area as the hilly Terrin of India are most disaster-prone, and MC -SDSS was used in GIS software for a better understanding. The findings of this research provide valuable insights for all tourism stakeholders in developing effective disaster management plans. By integrating risk management and vulnerability assessment into tourism planning processes, destinations can enhance their resilience to disasters, minimize economic losses, and ensure the safety of tourists and local communities.